2018
DOI: 10.22159/ajpcr.2018.v11i9.21885
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties of Pavetta Crassicaulis Bremek. Leaf and Flower Crude Extracts and Its Pure Compounds Collected From Western Ghats, Karnataka, India

Abstract: Objective: Pavetta crassicaulis Bremek. (F: Rubiaceae) plant extracts were subjected to anti-inflammatory experiment by using carrageenin-induced rat hind paw edema method.Methods: Groups of 5 rats of both sexes (pregnant females excluded) were given a dose of the extract. After 1 h, 0.1 ml, 1% carrageenan suspension in 0.9% NaCl solution was injected into the subplantar tissue of the right hind paw. Paw volume was measured plethysmometrically at 0 h and 3 h after carrageenin injection.Results: Anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hence, these results are representative of the potential of consumed vegetables to inhibit NO. A review of earlier studies showed similar antiinflammatory potentials of medicinal plants [23,24]. Likewise, turmeric from Curcuma longa has been shown to have interesting anti-inflammatory activity [25].…”
Section: Discussionmentioning
confidence: 95%
“…Hence, these results are representative of the potential of consumed vegetables to inhibit NO. A review of earlier studies showed similar antiinflammatory potentials of medicinal plants [23,24]. Likewise, turmeric from Curcuma longa has been shown to have interesting anti-inflammatory activity [25].…”
Section: Discussionmentioning
confidence: 95%
“…The ethanol extract of P. crassicaulis flowers showed an appreciable reduction in edema in all the phases and all the intervals, but the leaves extract outperformed the floral extract. However, both are more powerful than diclofenac [36].…”
Section: H Anti-inflammatorymentioning
confidence: 96%